Technology Assessment in Efficiency and Cost-effectiveness of Multislice CT Scan in Diagnosis of Cardiac and Coronary Artery Diseases - ตั้งสกุลวัฒนา, สุทารัตน์; สุพรรณชาติ, พงษ์ลดา; วิจิตรสงวน, ชมพูนุท; กออนันตกูล, ทวีทอง; แซ่จึง, บุญจง; ไหรัญพิจิตร, สุรภา (Journal of Health Science of Thailand, 2021)
This is a comparative study concerning the efficiency and cost of medical equipment used for the diagnosis of cardiac and coronary artery diseases. Due to the high costs and rapid changes in technology, factors such as unit price, maintenance, user-friendly operation, speed of reconstructive image and upgradeability must be assessed. Cost comparison between Magnetic Resonance Imaging (MRI) and 64-slice CT scanner was conducted. Recently developed, the 64 slice multidetector CT scan, can be seen as one of the most sensitive and specific tool in the diagnosis of coronary artery diseases. With the ability to produce high sensitivity of 94-95 percent, high specificity of 93-97 percent and high negative predictive value of 93-99 percent in diagnosis of cardiac especially coronary artery diseases, all cardiac centers must take notice of such an effective apparatus. Its break point even was 6.6 years while that of the MRI was 8.7 years.